Adolescent Brain Development: Implications for Understanding Risk and Resilience Processes through Neuroimaging Research - Morris, Amanda Sheffield (J Res Adolesc, 2018)
This special section focuses on research that utilizes neuroimaging methods to examine the impact of social relationships and socioemotional development on adolescent brain function. Studies include novel neuroimaging methods that further our understanding of adolescent brain development. This special section has a particular focus on how study findings add to our understanding of risk and resilience. In this introduction to the special section, we discuss the role of neuroimaging in developmental science and provide a brief review of neuroimaging methods. We present key themes that are covered in the special section papers including: 1) emerging methods in developmental neuroscience; 2) emotion-cognition interaction; and 3) the role of social relationships in brain function. We conclude our introduction with future directions for integrating developmental neuroscience into the study of adolescence, and highlight key points from the special section’s commentaries which include information on the landmark Adolescent Brain Cognitive Development (ABCD) study.